2012
DOI: 10.13005/bbra/981
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Glands Tumors: A Single Institution Experience in Saudi Arabia

Abstract: Salivary gland tumors (SGTs) are relatively uncommon with considerable variations in demographic distribution. Epidemiological data in relation to SGTs in Saudi Arabia are limited.The aim of this study was to determine the relative frequency SGTs and to compare the data with studies from different parts of the globe.The records of the Histopathology Laboratory of College of Dentistry, King Saud University during the period from1985 to2011 were reviewed. Tumors were classified according to the 2005 WHO classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Similar results were replicated by Pinkston et al [25]. On the contrary, a study by Feinstein MT et al and Sheddi MAA identified adenoid cystic carcinoma as the most common histologic variant [21-22].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were replicated by Pinkston et al [25]. On the contrary, a study by Feinstein MT et al and Sheddi MAA identified adenoid cystic carcinoma as the most common histologic variant [21-22].…”
Section: Discussionsupporting
confidence: 65%
“…The demographic distribution of this case-control study showed slightly more female distribution with the mean age of 44.4 years. In contrast, previous studies conducted by Feinstein MT et al and Sheddi MAA showed a male predominance [21-22].…”
Section: Discussionmentioning
confidence: 58%
“…Curiously no basal cell adenomas were reported in Asia and South America, whereas they comprised 5% of benign SGT in the UK and 3% in both European and African centres. This could be related to the smaller number of cases gathered from these centres or the lower incidence as previous studies have shown that basal cell adenoma is not within the most common five benign tumours in these regions [ 22 , 23 , 27 ]. The possibility of variation in diagnostic criteria can also not be excluded.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the peak prevalence of benign SGTs was in the 3rd decade, whereas malignant SGTs peak prevalence was in the 5th decade of life. It also reported that males are the predominant gender of all SGTs [7].…”
Section: Introductionmentioning
confidence: 93%